Perception of Students’ problems behaviour in teachers at mandatory secondary education - Gil Espinosa, F. J.; Delgado Noguera, M. A.; Chillón Garzón, P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
The learning environment influences the teaching-learning process as well as the welfare of the educational community members. Moreover, it is a question addressed by numerous scientific studies.The main objective of this research project is to describe and analyze the main conflicting behaviors of students in mandatory secondary education and relate to variables such as the location of institutions and participants, teacher gender, years of seniority as a teacher, management position and educational stage.In the research we worked with a sample of 147 teachers of Physical Education actively practicing in mandatory secondary education schools. Participants completed two ad hoc questionnaires to evaluate students´ problem behaviour at school. We followed the ‘factor analysis’ approach and finally we obtained five behavioural factors. We also applied the chi-squared test or so-called ‘Exact test of Fisher’ to associate these behaviours to other relevant variables. We conclude that the most frequent unruly behaviour are disruptive attitude and verbal abuse. Behaviours related to “Defiance and bullying” are more likely to happen when teachers are women. Less experienced teachers recorded more “attention deficit” behaviours in their classroom. Teachers having experience on management positions had to deal less often with behaviours related to “attention deficit” and “misuse of materials”.